Current bioinformatics tools for biodegradation of xenobiotic compounds - Arora, Pankaj Kumar; Kumar, Ashish; Srivastava, Alok; Garg, Sanjay Kumar; Singh, Vijay Pal (Frontiers in Environmental Science, 2022)
The review summarizes different bioinformatics tools used in studying the degradation of various xenobiotic compounds. Databases and Pathway Prediction Systems are the key bioinformatics tools involved in biodegradation. Several databases including EAWAG-BBD (Biocatalysis/Biodegradation Database), PMBD (Plastics Microbial Biodegradation Database), ONDB (Organonitrogen Degradation Database), FRCD (Food risk component database, Aromadeg (Aromatic hydrocarbon Degrading Database), OxDBase (A database of Biodegradative oxygenases), and RHObase database (aromatic ring-hydroxylating oxygenases) have been developed for biodegradation and bioremediation studies. Users can use pathway prediction systems to predict degradation of xenobiotic whose degradation has never been reported in the literature.